The Management of Seaweed Cultivation as an Educational Tourism Destination in Lembongan Village, Klungkung Regency, Bali: Manajemen Pengelolaan Budidaya Rumput Laut Sebagai Destinasi Wisata Edukasi di Desa Lembongan, Kabupaten Klungkung, Bali - Waruwu, Dermawan; R. Tri Priyono Budi Santoso; I Made Gde Sudyadnyana Sandhika (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2022)
Seaweed farming is one of the community's economic drivers in Lembongan Village, Klungkung Regency, Bali. In accordance with their individual regions or areas of production, these seaweed farmers are grouped into a number of groups. The conventional system is still used for managing seaweed cultivation. Tarpaulins are used by farmers to dry seaweed along highways or in open spaces. As a result, dust, sand, and other contaminants are present in seaweed. Because a tarp is all that is used to dry the seaweed, the procedure takes a while. Because it falls short of the requirements that collectors and purchasers need, seaweed has a poor selling price. Observation, interviews, document collecting, training, and mentorship for seaweed growers were used to study and assess this issue. Three topics related to seaweed farming are covered in this article: First, seaweed cultivation is still managed in a traditional manner. Second, a drying table, ultraviolet plastic, and green house technology must be used to dry seaweed. The quality and selling price of seaweed can be raised by good management and the application of technology during the drying process. Third, growing and drying this seaweed can be one of Lembongan Village's educational tourism (edutourism) attractions. This tourism location can draw more visitors from both local and international markets, boosting the economic benefits of seaweed farming. As a result, people are becoming more conscious of the need to protect the environment and are informed about the health and other benefits of seaweed.